Penguatan Kesiapsiagaan Gen Alpha melalui Komik Mitigasi Bencana Bertema Illegal Logging di SDN 02 Plalangan - Restu Ayu Eka Pustika Dewi; Rifky Rangga Arnawa; Elin Agni Nurul Qolbi; Siti Wahyuni; Isti Mulyawati (Pusat Riset dan Inovasi Nasional, 2025)
Illegal logging is one of the leading causes of environmental degradation, triggering natural disasters such as floods, landslides, and droughts. Children of Generation Alpha, who are still in the cognitive development stage, are considered vulnerable due to their limited understanding and preparedness for such disasters. This community service program aimed to enhance elementary school students’ awareness and knowledge of disaster mitigation through educational media in the form of printed comics. The activity was conducted by the KKN Team of Universitas Ivet Semarang at SDN Plalangan 02, involving 24 students from grades 3 and 4. The procedure consisted of preliminary observation to assess school needs, comic development on the theme of illegal logging-related disaster mitigation, delivery of the material through comic reading sessions, interactive discussions, and evaluation through pretest and posttest. The pretest results showed that most students were in the